Impact of Sodium-Glucose Cotransporter-2 (SGLT2) Inhibitors on Cardiovascular Events in Type 2 Diabetes - Shabbir, Hamza; Muhammad Rasikh; Bashir, Khalid; Ali Khan, Hamza; Khan, Hassaan Saeed; Raza, Mohsin; Shahid, Sayyed Hamza (Indus Journal of Bioscience Research, 2025)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder marked by persistent hyperglycemia and insulin resistance. Objective: The main objective of the study is to find the impact of Sodium-Glucose Cotransporter-2 (SGLT2) inhibitors on cardiovascular events in Type 2 diabetes. Methodology: This randomized control trial was conducted at Shalamar Hospital, Lahore, from 1st March to 31st August 2024. Data were collected from 195 patients. Data were collected at baseline and subsequent follow-up visits through standardized protocols. Results: Data were collected from 195 patients. Only 12.2% of patients in the SGLT2 inhibitor group experienced MACE, compared to 25.8% in the control group, reflecting a 52.7% relative risk reduction (p = 0.01). Similarly, heart failure hospitalizations were reduced to 5.1% in the SGLT2 inhibitor group compared to 15.5% in the control group, yielding a 67% relative risk reduction (p = 0.005). These findings highlight the significant cardiovascular protective effects of SGLT2 inhibitors. The Kaplan-Meier analysis revealed that patients in the SGLT2 inhibitor group had a significantly longer median time to the first cardiovascular event (11.5 months) compared to the control group (8.5 months), with a p-value of 0.002. Conclusion: It is concluded that sodium-glucose cotransporter-2 (SGLT2) inhibitors significantly reduce cardiovascular events in patients with type 2 diabetes mellitus, making them a pivotal advancement in diabetes management.